The Effect of Work-Life Balance and Transformational Leadership on Employee Turnover Intentions at Company X - Nurmalita Utami (CV. Publikasi Indonesia, 2025)
This research aims to identify the effect of work-life balance and transformational leadership on the turnover intentions of PT employees. X. Data obtained from the Company explains that the employee turnover rate in 2023 is 38.4%, which indicates that employee intentions to leave the company may also be quite high. Two predictors are raised to predict turnover intentions, namely work-life balance and transformational leadership, which are taken based on employee exit interview data. The research method used is a quantitative approach with a correlational analysis design to determine the relationship between predictor variables and outcome variables and multiple linear regression analysis to determine the magnitude of the influence of predictor variables on outcome variables. This study involved 245 respondents selected using purposive sampling techniques. The analysis results show that work-life balance and transformational leadership have a significant negative relationship with turnover intentions. In addition, work-life balance and transformational leadership also significantly negatively affect turnover intentions of 32.8%. The results of the multiple linear regression analysis show a significant negative influence value from the transformational leadership variable of t = -8.04 which is greater than the work-life balance variable of t = -4.31. The results of this study are expected to be input for companies to create programs or provide treatment for employees in order to improve transformational leadership and work-life balance to reduce the intention to move companies in employees and manage employee retention in the company.